2004
DOI: 10.1063/1.1640784
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond-laser-encoded distributed-feedback color center laser in lithium fluoride single crystals

Abstract: Laser-active F 2 centers were produced in lithium fluoride ͑LiF͒ at a concentration of 2 ϫ10 18 cm Ϫ3 by irradiating focused femtosecond ͑fs͒ laser pulses from a mode-locked titanium sapphire laser ͑wavelength ϳ800 nm, emission pulse duration ϳ100 fs). This technique was used to write waveguides embedded in LiF crystals. A refractive index change estimated from a guide propagation method was approximately ϩ1% at a wavelength of 633 nm. Refractive index-modulated volume-type gratings were also encoded inside Li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
54
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(54 citation statements)
references
References 15 publications
0
54
0
Order By: Relevance
“…In addition, recent advances in high-intensity femtosecond (fs) laser pulses have made it possible to fabricate small noble metal particles [9][10][11] such as gold and silver atoms embedded in glasses as well as encode various functional microstructures inside transparent materials [12][13][14]. In particular, such metal nanoparticles embedded in glasses are expected to 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 4 nanoparticles in Ag + -activated phosphate glass without heat treatment was demonstrated for the first time to clarify the origin of a RPL glass dosimeter by highly successive fs laser pulses.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, recent advances in high-intensity femtosecond (fs) laser pulses have made it possible to fabricate small noble metal particles [9][10][11] such as gold and silver atoms embedded in glasses as well as encode various functional microstructures inside transparent materials [12][13][14]. In particular, such metal nanoparticles embedded in glasses are expected to 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 4 nanoparticles in Ag + -activated phosphate glass without heat treatment was demonstrated for the first time to clarify the origin of a RPL glass dosimeter by highly successive fs laser pulses.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in high-intensity femtosecond (fs) laser pulses have made it possible to fabricate small noble metal particles such as gold and silver atoms embedded in glasses (Watanabe et al, 2001;Zhao et al, 2004;Shimotsuma et al, 2005) as well as encode various functional microstructures inside transparent materials (Kawamura et al, 2004;Kurobori et al, 2005;Kurobori et al, 2007). As far as silver-doped phosphate glass, Watanabe et al (2001) demonstrated a photosensitivity in soda-alumina-phosphate glass doped with Ag + upon exposure to ultraviolet (UV) fs laser pulses and found the formation of colour centres such as Ag 0 and Ag 2+ in the glass.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrafast laser processing has been extensively applied to fabricate 3D photonic devices such as optical couplers and splitters [84], volume Bragg gratings [85], diffractive lenses [86], Mach-Zehnder interferometers (MZIs) [87], and waveguide lasers [88,89]. Such photonic devices rely on the writing of 3D optical waveguides that can be easily inscribed in transparent materials such as glass, crystalline materials, and polymers by inducing permanent refractive index changes in the focal volumes of tightly focused ultrafast laser pulses [90].…”
Section: D Photonic Devicesmentioning
confidence: 99%